Poređenje analgetske efikasnosti blokova nerava pod kontrolom ultrazvuka pomoću tri anestetika različite dužine dejstva u lečenju rezistentnog neuropatskog bola donjih ekstremiteta - Jovanikic, Olivera; Andjelić, Gordana; Lepić, Milan; Mirković, Dušica; Jovanović, Bojan; Dragović, Tamara; Pavličević, Goran; Lepić, Toplica (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The neuropathic pain (NP) treatment is a big medical and socioeconomical problem. The new sorts of the NP treatment was developed and are applied in case of a medical treatment failure. The aim of this work was to investigate the efficacy of the ultrasound-assisted treatment of the resistant and chronic peripheral neuropathic pain with the local anesthetic nerve blocks. Due to the inefficacy of conventional treatment, three local anesthetics (short-acting, medium-term and long-acting) were administered in a series of the same minimal dose on a daily basis. Complications, side effects, the execution time of procedure and the onset time of local anesthetic were also investigated. Methods. In this prospective, randomized and double-blinded study, 108 patients (of which 53 were diagnosed with diabetes and 55 with radiculopathy) with the resistant and chronic peripheral neuropathic pain in the lower extremities were treated with a series of ultra-sound assisted peripheral nerve blocks. The conventional treatment was exhausted. The presence of this neuropathic pain was confirmed by, at least, one of the three scales – the Leeds Assesment of Neuropathic Simptoms and Signs (LANSS) scale, the Dolour Neuropathic 4 questions (DN4) scale and the pain DETECT(PD-Q) scale. Other therapies were not applied. The nerve blocks were administered on a daily basis until the relief of pain (visual analogue scale – VAS < 30), and after that, two additional nerve blocks were given. The three local anesthetics of the different duration of therapeutic effect were given at the same minimal dose: the schort-acting (1% procaine-chloride solution), medium-term (1% lidocaine-chloride solution) and long-acting (0.25% levobupivacaine-chloride solution) local anesthetics were used. The therapeutic efficacy was measured with the percentage reduction in the pain intensity on the VAS scale before and after the therapy and one month after the treatment: > 50% – excellent results; 31–49% – good results; < 30% the therapy did not work. The side effects, complications, the execution duration of procedure, the onset time of numbness, the number of corrections of the needle direction were recorded as well. Results. For all three groups: nerve blocks took 5.4 ± 1.48 minutes to do (withouth difference among the groups), the onset of numbness occured, on average, within 3.75 ± 2.62 minutes (withouth differences among the groups), and the need for corrections of needle direction was minimal (1.03 ± 0.17 corrections). All the patients experienced a loss of pain sensation (VAS < 30); when a long-acting anesthetic was used, the number of required nerve blocks was significant (p < 0.001) smallest (4.33 ± 0.63 blocks), than in other two groups, and the percentage pain reduction was highest (73.13%) (p < 0.001). The pain relief lasted one month after the therapy without the application of any other therapy. Neither complications nor side effects were observed. Conclusion. The procedure dercibed is a safe, efficient and easy-to-perform and does not lead to any complications and side effects. The pain relief is achieved most effectively and rapidly with the long-acting local anesthetics, and maintained even for one month without the introduction of any additional therapy.
Keywords: neuralgia; nerve block; ultrasonography; lower extremity